Augmented Reality Storytelling Pengenalan Benda Bersejarah di Minahasa Selatan: South Minahasa's Historical Object in Augmented Reality Storytelling - Lengkong, Gerry Riko; Lumenta, Arie S.M.; Rumagit, Arthur M. (Universitas Sam Ratulangi, 2024)
Historical objects are cultural assets that contains historical value which provides knowledge and overview about what happened in the past. Indonesia itself is a country that has various historical objects, Especially South Minahasa Regency ini North Sulawesi Province. South Minahasa Regency has numerous of historic relics such as Benteng Portugis, Veldbox Tumpaan, Waruga Popontolen, Menhir Lelema, and Lesung Batu Lutau Tondei. The rapid development of technology makes us more enjoyable to learn about those historical objects, for example using the Augmented Reality method. This research was conducted with the aim of making educative application that can introduce historical objects within South Minahasa Regency which developed using the MDLC (Multimedia Life Cycle) method. Based on the research and the results of the questionnaires that have been distributed, it can be concluded that there's an increase about user knowledge, and the introduction of historical objects can become more interactive to learn. Keywords: Augmented Reality, Historical Objects, South Minahasa.